EVALUASI PENGELOLAAN DANA DESA (Di Desa Kedaung Barat Kecamatan Sepatan Timur Kabupaten Tangerang): Array - Al Faruqi Nazaren; Adie Dwiyanto Nurlukman (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
This study aims to determine the evaluation of village fund management in accordance with PMK NO. 7 of 2016 especially in the field of facilities such as infrastructure development and also pre-facilities such as empowering rural communities. This research method uses a qualitative approach with a descriptive method in Kedaung Barat Village, East Sepatan District, Tangerang Regency, with data collection techniques of observation, interviews and documentation of relevant sources, data reduction, data presentation and conclusion drawing. The results showed that the use of village funds had prioritized to finance the implementation of local village-scale programs and activities in the field of village development and village community empowerment. However, there are several programs or policies on the use of village funds that are considered less than optimal if analyzed based on the theoretical indicators that the author uses, such as the leveling indicators, which are still not optimal.